2016
DOI: 10.1111/cico.12152
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Neighborhood Structural Conditions: The Effects of Concentrated Disadvantage on Homicide over Time and Space

Abstract: Several recent spatial analyses conclude the strong positive association typically found between neighborhood concentrated disadvantage and crime in cross‐sectional studies significantly differs across neighborhoods. It is possible this spatial variation is due to within‐neighborhood dynamics of continuity and change, as suggested by ecological theories of neighborhood crime. Using ordinary least‐squares and geographically weighted regression models, I explore the role of within‐neighborhood change on the disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 54 publications
5
21
0
Order By: Relevance
“…1 Theoretically, structural stability should have a positive effect on neighborhood organization, net of its level of disadvantage (or some other condition), producing lower-than-expected crime rates. Prior work supports this argument; Jacob H. Becker (2016) found that within-neighborhood changes in concentrated disadvantage between 1970-2000 partly accounted for spatial variation in the crosssectional association between disadvantage in 2000 and homicide in 2001-2005, and the results further suggested that changes in disadvantage were disruptive to the neighborhood and predictive of higher homicide rates. Within-neighborhood dynamics appeared to play an important role in the relationship between structural conditions and crime (at least homicide).…”
Section: The Dynamics Of Disadvantage Collective Efficacy and Homicidementioning
confidence: 92%
See 4 more Smart Citations
“…1 Theoretically, structural stability should have a positive effect on neighborhood organization, net of its level of disadvantage (or some other condition), producing lower-than-expected crime rates. Prior work supports this argument; Jacob H. Becker (2016) found that within-neighborhood changes in concentrated disadvantage between 1970-2000 partly accounted for spatial variation in the crosssectional association between disadvantage in 2000 and homicide in 2001-2005, and the results further suggested that changes in disadvantage were disruptive to the neighborhood and predictive of higher homicide rates. Within-neighborhood dynamics appeared to play an important role in the relationship between structural conditions and crime (at least homicide).…”
Section: The Dynamics Of Disadvantage Collective Efficacy and Homicidementioning
confidence: 92%
“…After the GWR procedure estimated the entire set of local regression parameters and statistics, a geographical variability test indicated there was significant spatial variation in the disadvantage parameter estimates across neighborhoods. This signified the level of disadvantage influenced homicide rates differently across NCs, as suggested by prior research (Becker 2016;Cahill and Mulligan 2007;Graif and Sampson 2009;Light and Harris 2012). Dummy variables of within-neighborhood changes in disadvantage were added to the model to examine if and how structural stability accounted for this spatial variation.…”
Section: Analytic Strategymentioning
confidence: 98%
See 3 more Smart Citations